MOLECULAR CHARACTERIZATION OF GENE 16S rRNA MICRO SYMBIONTS - Ismail Marzuki; Alfian Noor; Nursiah La Nafie; M Natsir Djide (Marina Chimica Acta, 2015)
Molecular characterization studies have been conducted 16S rRNA gene micro symbiont of sponge origin Melawai Beach, Balikpapan in East Kalimantan. Objective analysis of histomorphological research, isolation-purification, molecular characterization of micro-symbiont genes in order to search symbiont bacteria that can live in extreme environments contaminated hydrocarbon waste. The research method that morphological identification, isolation-purification and molecular characterization of the 16S rRNA gene with Chain Reaction Polymerization method. The results of histo-morphological analysis concluded sponge samples with species of Callyspongia sp Isolation and purification mikro symbionts of sponge obtained 2 (two) isolates. Characteristics of Isolates 1; spherical shape, colonize and creamy, while isolates 2; jagged shape, oval and white colonies. Molecular characterization of the 16S rRNA gene by PCR, Bacillus subtilis strain BAB-684 identification for isolates one is the number of nucleotide pairs reached 899 bp and the degree of similarity in GenBank reached 89% homologous, while the second is a Bacillus flexus strain PHCDB20 isolates the number reached 950 bp nucleotide pairs with the degree of similarity in GenBank reached 99% homologous.Keywords: Callyspongia sp, micro-symbionts, characterization, gene Molecules